A case of permeant neonatal diabetes with KCNJ11 mutation - V., Renjish; Cherian, Carol Sara; Abraham, Jacob; Koshy, Shanty Mary; Philiip, Rajeev (International Journal of Contemporary Pediatrics, 2023)
Neonatal diabetes mellitus is considered when there is hyperglycaemia requiring insulin therapy. Phenotypically NDM is classified into three types-transient, permanent and syndromic forms. Permanent NDM-may start in new-born life and is mainly due single gene mutations-KCNJ11 and ABCC8. This mutation is almost 90% manageable with oral sulphonyl ureas. We report a case of Permanent NDM with KCNJ11 mutation who presented in diabetic Ketoacidosis at 4 months of age. Clinical genome sequencing revealed a heterozygous missense variation in exon 1 of the KCNJ11 gene (chr11: g.17387491G>A) that results in the amino acid substitution of cysteine for arginine at codon 201. She was initially treated with insulin for which she had poor glycaemic control. She responded well following the switch over to sulphonylureas with good compliance and has normal development.